Implementation of Civil Aviation Safety in the World (Zien Journal of Social Sciences and Humanities, 2023)
This article discusses the implementation of measures and programs, including the objectives and functions of the International Civil Aviation Organization (WHO), in order to ensure the safety of civil aviation in the world.